Effects of the Air Inlet Angle on the Combustion and Ablation Environment of a Hybrid Powder-Solid Ramjet - Jinjin Wang; Yihao Wen; Bailin Zha; Zhigao Xu; Tianhao Zhang (International Journal of Aerospace Engineering)
A hybrid powder-solid ramjet (HPSR) that combined the advantages of a solid rocket ramjet (SRJ) and a powder ramjet engine was investigated in this research. To improve the combustion efficiency and optimize the inner wall thermal protection of the afterburner, the effects of the air inlet angle on the combustion and wall ablation environment were studied. The standard k-ε model, the eddy-dissipation model (EDM), and the boron particle ignition and combustion model were adopted to simulate the two-phase flow in the afterburners with different air inlet angles (45°, 60°, 75°, and 90°). The results showed that the global flow field and the distribution of the vortexes in the afterburner that had a significant influence on the ablation environment of the inner wall and the combustion efficiency were determined by the impact effect and the squeezing effect of the ram air on the primary fuel gas, which was affected by the air inlet angle. As the air inlet angle increased, the total combustion efficiency of the four cases first increased and then decreased, reaching 80.38%, 81.64%, 84.34%, and 83.26% for angles of 45°, 60°, 75°, and 90°, respectively. At the same time, the inner wall ablation became more severe because both the erosion effect of the condensed phase particles and the gas-flow scouring effect were enhanced, and a large temperature gradient was generated on the inner wall. The study results can provide a reference for designing the air inlet angle of an HPSR.